2013
DOI: 10.1371/journal.pone.0083621
|View full text |Cite
|
Sign up to set email alerts
|

Ail Proteins of Yersinia pestis and Y. pseudotuberculosis Have Different Cell Binding and Invasion Activities

Abstract: The Yersinia pestis adhesin Ail mediates host cell binding and facilitates delivery of cytotoxic Yop proteins. Ail from Y. pestis and Y. pseudotuberculosis is identical except for one or two amino acids at positions 43 and 126 depending on the Y. pseudotuberculosis strain. Ail from Y. pseudotuberculosis strain YPIII has been reported to lack host cell binding ability, thus we sought to determine which amino acid difference(s) are responsible for the difference in cell adhesion. Y. pseudotuberculosis YPIII Ail … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 48 publications
0
26
0
2
Order By: Relevance
“…Indeed loops 1 and 3 of Ail in Y. pestis are important for adherence and invasion, with up to 50% reduction in the abovementioned phenotypes when these two loops were mutated (65). However, similar levels of adherence and invasion of the ⌬lpp ⌬msbB::ailL2 and the ⌬lpp ⌬msbB ⌬ail triple mutants in HeLa cells signified the important role of loop 2 in Ail-associated virulence phenotypes and also suggested that a conformational association between various loops of Ail might be necessary for efficient bacterial adherence to and invasion of the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed loops 1 and 3 of Ail in Y. pestis are important for adherence and invasion, with up to 50% reduction in the abovementioned phenotypes when these two loops were mutated (65). However, similar levels of adherence and invasion of the ⌬lpp ⌬msbB::ailL2 and the ⌬lpp ⌬msbB ⌬ail triple mutants in HeLa cells signified the important role of loop 2 in Ail-associated virulence phenotypes and also suggested that a conformational association between various loops of Ail might be necessary for efficient bacterial adherence to and invasion of the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ail is the most critical adhesion molecule, followed by Pla and then Psa (75). We have shown that the levels of Pla and F1 as well as the enzymatic activity of Pla were not affected in the ⌬lpp ⌬msbB ⌬ail triple mutant ( Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Although Y. pestis is a facultative intracellular pathogen (2), its ability to invade epithelial cells has been reported only recently (33,44,61,75). Ail is a major mediator responsible for the adherence and invasion of Y. pestis KIM strains or when the ail gene is overexpressed in nonadherent and noninvasive E. coli strains in human epithelial cells of cervical origin (HeLa and Hep-2) (33,34,44,45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously characterized the different functions of Y. pestis Ail, including adhesion to host cells, binding to purified Fn and Ln, and facilitation of Yop delivery (1,8,(13)(14)(15)32). These previous studies led us to identify the minimal binding site for Ail on Fn, a stretch of just 180 amino acids in the 250-kDa Fn protein molecule.…”
Section: Discussionmentioning
confidence: 99%